A Comparative Analysis of Dholuo and Lubukusu Anaphors within the Government and Binding Theory - (:unkn) unknown (My University, 2023)
Languages exhibit anaphors, reflexives and reciprocals as either lexical items or affixes. This makes it interesting to identify their occurrence and interpretation. The study aimed at comparing anaphoric system of two African languages: Dholuo and Lubukusu to establish their morphological configuration and syntactic properties. Corpus of data for study were drawn from different sources. Dholuo data was derived from native speaker intuition, elicitations and from existing work by scholars. Lubukusu drawn was derived from works from scholars. First, data was categorized to establish their configuration. Then, the data from Dholuo and Lubukusu were compared to establish their morphological and syntactic configuration. Thereafter, a comparison of the anaphors from the two languages was performed. Syntactically, the anaphors were descriptively analyzed using X-bar syntax and Binding Theory modules of the Government and Binding Theory (GB). Results indicate that the two languages belong to different families: Dholuo, a Nilotic language while Lubukusu Bantu. Typologically, both Dholuo and Lubukusu were found to be agglutinating languages characterized with presence of affixes. Similarly, the affixes are bound to the verb. Contrastively, Lubukusu contains reflexives which occur as prefixes and reciprocals as suffixes; while Dholuo anaphors occur as suffixes. Conversely, Lubukusu exhibit the reflexive which occurs as an allomorph with two different morpheme markers; whereas Dholuo has a single reflexive marker. Furthermore, Lubukusu’s reciprocal is distinctly marked while in Dholuo the reciprocal and the reflexive are marked with the same morpheme. Apparently, context is paramount in the interpretation of Dholuo anaphor whereby both the speaker and listener must be aware of what is being conveyed. Lastly, both languages met the conditions highlighted in Chomsky’s Binding Principle A in establishing grammaticality of constructions. The anaphors are bound to
Keywords: African Research